USE OF MODERN INFORMATION TECHNOLOGY IN TRAINING ENGINEERING PROFESSIONALS - Y. Gladkiy; V. Milko (Kherson State University, 2010)
The article deals with current learning technologies and analyzes the characteristics necessary for successful systems operation based on modular environment. The experience of the preparation of engineering skills-based course «Operation and maintenance of machinery» with LMS has been shown.